PELATIHAN PENGELOLAAN KEUANGAN BISNIS BAGI REMAJA PUTUS SEKOLAH DI KELURAHAN MARTIGUNA - Pelipa, Emilia Dewiwati; Marganingsih, Anna; Seran, Eliana Yunitha (STKIP Persada Khatulistiwa Sintang, 2024)
service activities in 2023 were carried out in Martiguna village, Sintang sub-district, Sintang district, West Kalimantan. This service activity raises the theme of financial management for teenagers who drop out of school or are unemployed. They will be given training in financial management of a business with the aim that these teenage dropouts can start their own business. This training on financial management of a business is carried out due to the difficulty of employment at this time, so that rural communities, especially those who drop out of school or are unemployed, can have the knowledge to start a business both in terms of capital, financial arrangements and strategies for starting a business.